2007
DOI: 10.5194/nhess-7-155-2007
|View full text |Cite
|
Sign up to set email alerts
|

A perturbation of DC electric field caused by light ion adhesion to aerosols during the growth in seismic-related atmospheric radioactivity

Abstract: Abstract. The influence of variations in conductivity and external electric current variations in the lower atmosphere on DC electric field over a seismic region is investigated. The external current is formed with the occurrence of convective upward transport of charged aerosols and their gravitational sedimentation in the atmosphere. This effect is related with the occurrence of ionization source due to seismic-related emanation of radon and other radioactive elements into the lower atmosphere. An increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…There have been opposite views about if the electric fields excited by earthquake can penetrate into the ionosphere. Some has concluded that electromagnetic waves can penetrate into the ionosphere (Kim et al, 1994;Pulinets et al, 2000;Sorokin et al, 2001Sorokin et al, , 2007, but the others hold opposite views, that the electromagnetic energy released by earthquakes is too weak to be observed at satellite altitudes (Densisenko et al, 2008;Ampferer et al, 2010). Therefore, based on the current detection ability of satellites, the minimum electric field at the bottom of the ionosphere is also calculated by our new model in this study.…”
Section: S F Zhao Et Al: the Numerical Simulation On Ionospheric Pmentioning
confidence: 79%
“…There have been opposite views about if the electric fields excited by earthquake can penetrate into the ionosphere. Some has concluded that electromagnetic waves can penetrate into the ionosphere (Kim et al, 1994;Pulinets et al, 2000;Sorokin et al, 2001Sorokin et al, , 2007, but the others hold opposite views, that the electromagnetic energy released by earthquakes is too weak to be observed at satellite altitudes (Densisenko et al, 2008;Ampferer et al, 2010). Therefore, based on the current detection ability of satellites, the minimum electric field at the bottom of the ionosphere is also calculated by our new model in this study.…”
Section: S F Zhao Et Al: the Numerical Simulation On Ionospheric Pmentioning
confidence: 79%
“…From the observations of ionospheric perturbations associated with large earthquakes, several models have been proposed to explain the seismo-ionospheric coupling mechanism; these include an electromagnetic-wave-penetrating model from the lithosphere to the ionosphere (Molchanov et al, 1995), an acoustic-wave-propagating model (Hegai et al, 1997) and electrical-field-coupling models related to radon emission, aerosol accumulation, rock current and surface charge (Pulinets, 2004(Pulinets, , 2009Sorokin et al, 2007;Kuo et al, 2011). The last model plays an important role in explaining the ionospheric disturbances related to seismic activities in plasma parameters, such as the perturbations in GPS TEC (total electron content), foF2 and electron density; The histogram of distribution probability at different correlation coefficients before and after global earthquakes (in the right corner of the panel, the exponential decay has been fitted between the counts (variable y) and different coefficient scales (variable x); furthermore, the correlation coefficient R has been calculated).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of modifications of the quasi-constant electric field related to earthquakes have been already studied for some decades (Gokhberg et al, 1988;Morgunov, 1998;Vershinin et al, 1999;Pulinets et al, 2000;Mal'zev and Morgunov, 2005;Sorokin et al, 2006Sorokin et al, , 2007. In these works, anomalies of the temporal behaviour of the vertical component of the quasi-stationary electric field were analysed, which were connected with earthquakes for which already known meteorological phenomena were not obtained.…”
Section: Local Pulses Of the Atmospheric Electric Field -A Possible Rmentioning
confidence: 99%